Clinical outcomes of non–small cell lung cancer patients with leptomeningeal metastases after immune checkpoint inhibitor treatments. (June 2021) - Zheng, Mei-Mei; Tu, Hai-Yan; Yang, Jin-Ji; Zhang, Xu-Chao; Zhou, Qing; Xu, Chong-Rui; Jiang, Ben-Yuan; Yang, Xue-Ning; Yang, Xiao-Rong; Deng, Jia-Yi; Yang, Ming-Yi; Xu, Bing-Fei; et al.
Abstract: Objective: Leptomeningeal metastases (LM) occur in up to 5% of non–small cell lung cancer (NSCLC) patients and often develop after previous systemic treatments. In this article, we explored whether immune checkpoint inhibitors (ICIs) enhanced the dismal survival of patients with LM. Materials and methods: Data on NSCLC patients with LM prescribed ICIs were collected at the Guangdong Lung Cancer Institute. Furthermore, relevant literature was reviewed. Results: A total of 255 NSCLC patients diagnosed with LM were screened from January 2015 to March 2020 at our institute. Cases reported by literature were also included. Finally, 32 NSCLC patients received ICIs after LM diagnosis; their median age was 55 years. Druggable genes were detected in 37.5% of all patients. The ICI regimens included nivolumab (n = 21), pembrolizumab (n = 9), and atezolizumab (n = 2). Ultimately, 62.5% of patients evidenced neurological symptom controlled. Two patients exhibited both intracranial and extracranial complete tumour response; one patient showed both intracranial and extracranial partial response (PR), one patient indicated intracranial PR and a systemic PR, and one patient showed central nervous system PR without extracranial response reported. The median progression-free survival (PFS) in the single-agent subgroup was 2.1 months (95% confidence interval [CI]: 1.4–2.9 months), and the median overall survival (OS) was 4.0 months (95% CI: 0.1–13.3 months). In the combined subgroup, the median PFS and OS were 3.0 months (95% CI: 1.1–4.9 months) and 5.4 months (95% CI: 0.5–10.3 months), respectively. Three patients exhibited remarkable PFS of over 20 months: all patients had ICI single agent, received cranial radiotherapy before ICI prescription, and took ICIs as second-line therapy, and two patients were EGFR / ALK wild type. Multivariate analysis showed that a better Eastern Cooperative Oncology Group Performance Status (ECOG-PS) score was associated with prolonged PFS ( P  = 0.04). No difference in survival was seen between monotherapy and combination therapy groups. Conclusion: NSCLC patients with LM may benefit from ICIs of both monotherapy and combination with other therapies, especially those with good ECOG-PS scores. Further work in this regard is required. Highlights: Selected NSCLC patients with leptomeningeal metastases might benefit from ICIs. ECOG-PS score is related with outcome of ICIs in leptomeningeal metastases. Our study support ICIs as one of the options for some leptomeningeal metastases.